(untitled) (ARQUISUR Revista, 2020)
This article aims to investigate the flexibilization of urban planning instruments in relation to urban density. To this end, it takes as a case study the city of Passo Fundo / RS, where it was observed that the Plano Diretor de Desenvolvimento Integrado (PDDI), instituted in 2006, went through a series of changes related to the proposed urban regime. To achieve the objective, legal acts were analyzed, identifying those related to the planning of urban densities. Subsequently, synthesis maps of urban indexes were used, making it possible to spatialize the changes and analyze them comparatively. Finally, through the Spatial Syntax Analysis, it was possible to characterize the locations in terms of their integration / segregation. As a conclusion, it was found that the flexibilization of the PDDI occurred mainly in areas of low integration and that its appropriation to urban materiality already occurs, mainly due to the type of condominiums of the Minha Casa, Minha Vida program, destined to low / medium income.